2021
DOI: 10.1016/j.jcot.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial balloon spacer – Where are we now?

Abstract: Introduction: Rotator cuff tears are a common cause of disability and pain. The ideal treatment for truly irreparable rotator cuffs is still debated, and one recent surgical advance is the development of the subacromial balloon spacer. This review aims to clarify the current evidence and indications for this device. Methods: A comprehensive literature search was undertaken using the MeSH search terms combining "balloon spacer" and "irreparable cuff tear". A total of 20 studies using the balloon spacer as a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…The subacromial balloon spacer has been introduced as a novel surgical technique in shoulder surgery with great therapeutic potential in the domain of irreparable rotator cuff tears [ 9 ]. This device is made from a biodegradable and bioabsorbable polymer, with properties that ensure both the elasticity and strength required to be introduced in the subacromial space and alleviate any concurrent impingement [ 10 , 11 , 12 , 13 ]. Evaluation of the safety profile of the device showed no evidence of systemic toxicity or chronic body reaction after its introduction into the body [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subacromial balloon spacer has been introduced as a novel surgical technique in shoulder surgery with great therapeutic potential in the domain of irreparable rotator cuff tears [ 9 ]. This device is made from a biodegradable and bioabsorbable polymer, with properties that ensure both the elasticity and strength required to be introduced in the subacromial space and alleviate any concurrent impingement [ 10 , 11 , 12 , 13 ]. Evaluation of the safety profile of the device showed no evidence of systemic toxicity or chronic body reaction after its introduction into the body [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This device is made from a biodegradable and bioabsorbable polymer, with properties that ensure both the elasticity and strength required to be introduced in the subacromial space and alleviate any concurrent impingement [ 10 , 11 , 12 , 13 ]. Evaluation of the safety profile of the device showed no evidence of systemic toxicity or chronic body reaction after its introduction into the body [ 10 ]. As a result, and over the recent years, the balloon has been considered a viable and safe option for many rotator cuff patients, whose presentation fits the indications and contraindications of its placement.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies published recently have shown favorable results. 18 , 22 , 24 Notably, Stewart et al 18 conducted a systematic review that included 12 studies for final analysis showing improvements in mean Constant Scores from 18.5 to 49.6 at an average of 22.9 months after implantation. These studies also describe similarly low rates of complications, revision surgeries, or clinical failures.…”
Section: Discussionmentioning
confidence: 99%
“…12 Insertion of a biodegradable balloon in the subacromial space to reduce acromio-humeral contact and aid deltoid function has also been explored. 13 Such "disruptive" technologies seek to lower the surgical risks and morbidities associated with tendon transfers which require a more extensive surgical dissection. 14 Ever-increasing management options for the challenging cuff notably include Reverse Shoulder Arthroplasty (RSA).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%